Do indigenous firms incur a liability of localness when operating in their home market? The case of China - Jiang, Fuming; Stening, B. (ELSEVIER, 2012)
Liability of foreignness has been one of the building blocks of theories of multinational enterprises. This paper looks at a parallel issue - the liability of localness that local firms may face as a result of foreign firms’ presence in their country. The results show that local Chinese firms enjoy location-based advantages over their foreign counterparts and these, together with their firm-specific advantages, have significant positive effects on their performance. The superior firm-specific advantages of foreign firms appear to erase the magnitude of such effects and create a significant negative impact on local Chinese firms’ performance, and this effect is heightened by foreign firms’ multinationality advantages. The research suggests that local Chinese firms incur a liability of localness, and the extent of the negative impact of such liability on local firm performance is largely dependent on the relative strength of various advantages that the local and foreign firms possess.